A review on heat and mechanical energy harvesting from human – Principles, prototypes and perspectives. (February 2018) - Zhou, Maoying; Al-Furjan, Mohannad Saleh Hammadi; Zou, Jun; Liu, Weiting
Abstract: The rapid development of smart electronics has enabled their applications into such fields as portable instruments, wearable electronic devices, implantable medical devices and even assistive biomedical devices. As a result, power requirements of these devices continuously increase to such a degree that currently used batteries can not meet. Recently the heat and mechanical energy available in human daily activities have received increasing attention by researchers as alternatives. This paper looks into the physical mechanisms, materials and devices involved in possible energy harvesting from human motion. Heat and mechanical energy available in human daily activities are summarized to give an overview of the potential of energy harvesting from human motion. In addition, different energy transducing principles are discussed. Moreover, various proposed or demonstrated energy harvesting prototypes related to human motion are reviewed and discussed with respect to their working principles, device structures, implementations and performances. Finally, trends, challenges, applications and future developments of energy harvesting from human motion are discussed.